Scoping review of studies on food marketing in Latin America: Summary of existing evidence and research gaps - Chemas-Velez, Maria Manuela; Gómez, Luis F.; Velasquez, Alcides; Mora-Plazas, Mercedes; Parra, Diana C. (Revista de Saúde Pública, 2020)
OBJECTIVE: To document the evidence about marketing of ultra-processed foods and “non-alcoholic” beverages in Latin America. METHODS: We performed a structured search of quantitative and qualitative studies in PubMed, SciELO and LILACS, published between January 2000 and May 2017 and conducted in Latin America. We conducted a quality assessment following a standardized tool and a thematic analysis to identify key typologies of marketing across studies RESULTS: Out of 521 studies screened by title and abstract, we included 36 in this review; 27 of them analyzed television advertisement. Other marketing channels studied were food packaging, point of sale and outdoor advertisement. Studies found television advertises foods and beverages that are mostly ultraprocessed foods and have low nutritional value, particularly those promoted during children’s programming. We also observed children have a literal interpretation of images printed on food packaging, so this can be deceiving. Several studies also found proximity to unhealthy foods may increase their consumption. Finally, the thematic analysis identified the following typologies of food marketing: a) television advertisement, b) food packaging marketing, c) marketing strategies at points of sale and d) other marketing strategies. We found almost no advertisements for unprocessed or minimally processed foods such as fruits and vegetables. We did not find any studies on digital marketing conducted in the region. CONCLUSIONS: This review found that the main channel of food marketing was television advertising. This synthesis provides insights to the challenges unhealthy eating represents to the public health of Latin America and identifies knowledge gaps to guide future research.